HUBUNGAN PERSEPSI DENGAN PARTISIPASI MASYARAKAT SEKITAR EKOWISATA MANGROVE DI KABUPATEN MEMPAWAH - Puput Ningsih; Eva Dolorosa; Imelda imelda (Jurnal Sains Pertanian Equator, 2019)
Participation is community involvement in the process of planning, implementation, utilization and evaluation. This study aims to determine the relationship of perceptions with community participation on mangrove ecotourism. The study was conducted on communities around the Polari Ecotourism of Tanjung Pagar in Mendalok Village, Sungai Kunyit Subdistrict, Mempawah Regency with 100 respondents taken by simple random sampling. Analysis of community perception is measured from economic aspects and ecological aspects. The relationship of each variable is measured using Spearman rank correlation. The results of the analysis state that the public perception of the economic aspects is good, because the existence of mangrove ecotourism provides additional income for the community, and viewed from the ecological aspects of community perception is also good, because the existence of mangrove ecotourism in the neighborhood is clean, well maintained, and protected by the presence of trees mangrove tree. Community participation is high, seen from the enthusiasm of the community involved in planning, implementing, utilizing, and evaluating every activity carried out in mangrove ecotourism. Thus, there is a strong relationship between perceptions and community participation, which means that if people's perceptions are increased then community participation also increases.Keywords: Perception , Participation, Ecotourism, Mangrove, Mempawah District.